2018
DOI: 10.4103/jgid.jgid_86_17
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired lower urinary tract infections: Etiology, antimicrobial resistance, and treatment results in female patients

Abstract: Background/Purpose:Most community-acquired urinary tract infections (UTIs) are usually treated empirically. The knowledge of antibiotic resistance patterns of the microorganisms causing UTI is essential for defining the empirical treatment.Objective:The aim of the present study is to determine the distribution of bacterial strains isolated from lower UTIs and their resistance patterns against commonly used antimicrobial agents and treatment results in female patients.Subjects and Methods:This is a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 23 publications
8
37
0
Order By: Relevance
“…Other ESBL producing Enterobacteriaceae detected in Turkey include CTX-M/TEM/SHV/qnrA aac(6′)-ib Enterobacter spp. and VEB-1/qnrA1 Providencia stuartii (Nazik et al, 2009, 2011; Erdem et al, 2018). Interestingly, Agin et al (2011) reported an outbreak of Salmonella enterica serovar typhimurium producing SHV-12 and CTX-M-3 ESBLs.…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…Other ESBL producing Enterobacteriaceae detected in Turkey include CTX-M/TEM/SHV/qnrA aac(6′)-ib Enterobacter spp. and VEB-1/qnrA1 Providencia stuartii (Nazik et al, 2009, 2011; Erdem et al, 2018). Interestingly, Agin et al (2011) reported an outbreak of Salmonella enterica serovar typhimurium producing SHV-12 and CTX-M-3 ESBLs.…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…The microbial spectrum of UTIs mainly consists of Escherichia coli, and other uropathogens such as Staphylococcus saprophyticus, Enterococcus, Proteus sp., Pseudomonas aeruginosa, Candida albicans, and Klebsiella pneumonia are rarely isolated from UTIs [12]. Enterobacteriaceae is a diverse group of pathogens that accounts 80% of gram-negative bacterial isolates that cause various diseases in humans, including urinary tract infections [13].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] In it, they found E. coli to be the most common organism and 32% of them were extended-spectrum beta-lactamase (ESBL) producing. [ 6 ] In their study, fosfomycin and nitrofurantoin were found to be the drugs with least resistance and highest eradication rate. However, in the Norwegian study, nitrofurantoin resistance was quite high.…”
mentioning
confidence: 99%